PENERAPAN HYGIENE DAN SANITASI DI DAPUR À LA CARTE NAGOYA MANSION - Meilina, Cindy; Saputra, Eryd; Nuryanto, Heri (JURNAL MEKAR, 2024)
Implementing hygeiene and sanitation in the kitchen is very important to improve the quality of the restaurant. Hygeiene is cleanliness, while sanitation is an attempt to maintain and protect food from unwanted subjects. Hotel Nagoya Mansion Batam is a 4-star hotel located in Batam City, Riau Islands. In 2019 the Nagoya Mansion hotel implemented hygeiene and sanitation in the public kitchen. The impact of covid-19 on the hotel has made Nagoya Mansion no longer use its public kitchen, and only uses the À La Carte kitchen. Thus, research was conducted on the À La Carte kitchen of the Nagoya Mansion. The existence of this hotel has an effect on increasing the number of tourists in Batam City. To be able to produce food and beverages of good quality, healthy, and liked by guests, the hotel must implement hygeiene and sanitation, especially for employees who work in food and baverage products. The formulation of the problem in this research is how the process of storing raw materials, processing raw materials, and serving food at the Nagoya Mansion Hotel Batam is. The purpose of this study was to determine the application of Hygeiene and Sanitation at the Nagoya Mansion Hotel Batam, precisely in the A la carte kitchen. The benefit of this research is to gain insight and knowledge to the readers as a reference material, especially those who are involved in the field of hospitality tourism. In this study the method used is a qualitative method through participatory observation by collecting data analysis techniques carried out directly in the A la carte kitchen of the Nagoya Mansion Hotel Batam.